Antimicrobial activity of actinomycetes isolated from mangrove soil in Tuban, East Java, Indonesia - FATIMAH FATIMAH; FATICHATUS SUROIYAH; NIKMATUS SOLIKHA; NAZIL DWI RAHAYUNINGTYAS; TINI SURTININGSIH; TRI NURHARIYATI; NI’MATUZAHROH NI’MATUZAHROH; MOCH. AFFANDI; ALMANDO GERALDI; AHMAD THONTOWI (Society for Indonesian Biodiversity, 2022)
Abstract. Fatimah, Suroiyah F, Solikha N, Rahayuningtyas ND, Surtiningsih T, Nurhariyati T, Ni’matuzahroh, Affandi M, Geraldi A, Thontowi A. 2022. Antimicrobial activity of actinomycetes isolated from mangrove soil in Tuban, Indonesia. Biodiversitas 23: 2957-2965. This study aims to isolate, identify, and investigate the antimicrobial activity of actinomycetes isolated from mangrove soil of the Mangrove Center Tuban in Jenu Village, Tuban District, Indonesia. Soil sampling was carried out with a purposive sampling technique. The dry-heating and pour plate methods were used to isolate actinomycetes. Four isolates (LIB.2; LIA.4; LIA.9; and LIA.10) were selected and tested for their antimicrobial activities against Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923, and Candida albicans ATCC 10231 using disc diffusion method. Colony morphology characterization and Gram staining were then conducted on the 4 isolates. The identification of LIB.2 was performed by biochemical assay and 16S rRNA gene sequence analysis. The results showed that crude antimicrobial extracts (CACs) of all isolates inhibited the growth of E. coli but not S. aureus and C. albicans. Isolate LIB.2 showed the highest inhibition zone with a diameter of 15,65 ± 2,33 mm, followed by LIA.9 (10,19 ± 2,78 mm), LIA.4 (9,80 ± 0,47), and LIA.10 (8,75 ± 0,42 mm). The most potential isolate was identified as a member of Streptomyces genera. Based on biochemical assay and 16S rRNA gene sequence analysis, LIB.2 was identified as Streptomyces vellosus strain LIB.2.